N-Heterocyclic carbene-catalyzed synthesis of alpha-trifluoromethyl esters - Gelat, Fabien; Patra, Atanu; Pannecoucke, Xavier; Biju, Akkattu T.; Poisson, Thomas; Besset, Tatiana (Organic Letters, 2018)
The N-heterocyclic carbene (NHC)-catalyzed trifluoromethylation of alpha-chloro aldehydes was developed, allowing straightforward access to valuable alpha-trifluoromethyl ester derivatives. The unique combination of an electrophilic trifluoromethylation reagent with NHC catalysis was the key for the functionalization of a broad range of alpha-chloro aldehydes, and the products are formed in moderate to good yields. Investigations of the enantioselective version of this reaction afforded the enantioenriched products in moderate yields with good ee values.